ANALISIS KOMPARASI KINERJA KEUANGAN ATAS IMPLEMENTASI KEBIJAKAN TAX AMNESTY (Studi Kasus pada PT. Bank Rakyat Indonesia (Persero), Tbk) - Retnani, Gitta Wahyu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Tax amnesty is the government’s policy to stimulate state revenue from tax sector for accelerating national development. Tax amnesty funds, especially repatriation funds, are submitted by the third party to the banks appointed as perception banks. This research aims to compare the financial performance before and after the implementation of tax amnesty policy phase II and the repatriation fund projection, as well as to relate the financial performance and earnings by the end of tax amnesty policy phase III implementation. The study is administered at PT. Bank Rakyat Indonesia (Persero) Tbk, one of the perception banks in Indonesia. The data are analyzed by means of Wilcoxon test toward the financial performance ratio calculation, which consist of LDR, NPL, CAR, ROA, BOPO and NIM. Besides, the projection is examined by least square trend, regression, and expected value analysis. The result of the study shows that bank financial performance has improved during the implementation of tax amnesty. When the estimated third party fund from repatriation to BRI can be obtained optimally and is likely to improve bank financial performance, the earnings can also be maximally gained.Keywords: Tax Amnesty, Repatriation Fund, Third Party Fund, Bank Financial Performance, Earnings.